Participação e deliberação na internet: um estudo de caso do orçamento participativo - Marques, Francisco Paulo Jamil Almeida (2011)
This paper aims to examine how political conversations take place on the online forum offered as part of the Digital Participatory Budget (OPD) in a Brazilian city, Belo Horizonte. The authors propose an analytical model based on deliberative theories in order to investigate the discussions over this participatory program. The main sample consists of the messages posted by the users (n=357) on the commentaries section. The results show that reciprocity and reflexivity among interlocutors are rare; however, the respect among the interlocutors and the justification levels in several arguments were high during the discussion. The authors conclude that, even in a situation in which there is no empowerment offered by of the digital tools, the internet can effectively provide environments to enhance a qualified discursive exchange. In spite of low levels of deliberativeness, the case study shows that there are important gains concerning social learning among the participants.